Current Developments in Optical Fiber Technology - Wadi Harun, Sulaiman; Arof, Hamzah (IntechOpen, 2013)
This book is a compilation of works presenting recent advances and progress in optical fiber technology related to the next generation optical communication, system and network, sensor, laser, measurement, characterization and devices. It contains five sections including optical fiber communication systems and networks, plastic optical fibers technologies, fiber optic sensors, fiber lasers and fiber measurement techniques and fiber optic devices on silicon chip. Each chapter in this book is a contribution from a group of academicians and scientists from a prominent university or research center, involved in cutting edge research in the field of photonics. This compendium is an invaluable reference for researchers and practitioners working in academic institutions as well as industries.